Reducing speckle artifacts in digital holography through programmable filtration. Issue 1 (30th January 2019) - Lim, Yongjun; Park, Jae‐Hyeung; Hahn, Joonku; Kim, Hayan; Hong, Keehoon; Kim, Jinwoong
Abstract : We propose a speckle reduction technique in electronic holographic display systems, where digital micro‐mirror array devices are used as spatial light modulators. By adopting a programmable filtration in a general 4‐ f optic configuration, it is shown that the signal spectrum components in the frequency domain of a viewing‐window‐based holographic display system can be selectively filtered. Compared to the widely utilized single‐sideband filtration techniques in electronic holographic display systems, our proposed programmable filtration can be utilized to effectively reduce the speckles in the reconstruction of point‐cloud‐based computer‐generated holograms. Experimental results are presented to verify our proposed concept.